ANALISA PENGARUH BEBAN PAJAK PENGHASILAN TAHUN SEBELUMNYA TERHADAP AKTIVITAS MANAJEMEN LABA TAHUN BERJALAN DENGAN MENGGUNAKAN UKURAN PERUSAHAAN DAN LEVERAGE SEBAGAI VARIABEL KONTROL - Nikki Mulia Candra; Yulius Jogi Christiawan (Business Accounting Review, 2017)
This study aimed to examine the affect of income tax expense of prior year on earnings management activities of current year of mining public companies in Indonesia by using firm size and leverage as control variables. Samples of this research selected with purposive sampling method. The data obtained from 41 financial reports of mining public companies that registered in Indonesia Stock Exchange from 2010 until 2015.The Modified Jones model was used to calculate Discretionary Accrual which became a proxy of earnings management. Income tax expense measured by dividing tax expense of prior year with total assets of the end of the year. Then firm size was calculated by log of total asset of current year whereas leverage was measured by dividing total long term debt of current year with total asset of current year by using multiple linear regression analysis.The results showed that income tax expense, firm size, and leverage had affect on earnings management simultaneously. Income tax expense had negative influence on earnings management, on the other side firm size had positive effect on earnings management. However, leverage had no effect on earnings management.